Aspergillus Thyroiditis after Allogeneic Hematopoietic Stem Cell Transplantation. (12th November 2015) - Ataca, Pinar; Atilla, Erden; Saracoglu, Pelin; Yilmaz, Gulden; Civriz Bozdag, Sinem; Toprak, Selami Kocak; Yuksel, Meltem Kurt; Ceyhan, Koray; Topcuoglu, Pervin
Abstract : Aspergillus thyroiditis is a rare disorder detected in immunocompromised patients during disseminated infections. Early management is essential to prevent high mortality. A 61-year-old allogeneic stem cell male recipient presented with painful thyroid nodular enlargement. He had low TSH and low free T4 levels. The thyroid ultrasound showed a hypoechoic nodule; biopsy indicated suppurative Aspergillus thyroiditis. He was successfully treated by amphotericin B.